The Importance of Place in Contemporary Terrorist Attacks – Conclusions for Designing an Institutional Response - Stelmach, Jarosław (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2024)
The purpose of the research, the results of which are included in this publication, was to develop general conclusions regarding the conduct of counterterrorism operations in the context of the place of a terrorist attack. Thus, the identified subject and purpose of the research determined its categorization as applied and embedded in the discipline of security sciences. Corresponding with the purpose of the research process is the research question – what recommendations and conclusions related to the place of a terrorist attacks can be crucial for designing an institutional response? The author assumed in the research hypothesis the possibility of deriving such valuable conclusions that can contribute to strengthening the qualitative response to contemporary terrorist attacks. The research described in the text was based on scientific methods in the form of literature analysis and criticism, document analysis, comparative analysis, cross-sectional synthesis and multiple immersion case studies. The research results obtained became the basis for the development of key conclusions that should be taken into account in the preparation of solutions for institutional response to contemporary terrorist attacks. Celem badań, których wyniki zawarto w niniejszym artykule, było wypracowanie ogólnych wniosków dotyczących prowadzenia działań antyterrorystycznych w kontekście miejsca ataku terrorystycznego. Tym samym identyfikowany przedmiot i cel badań przesądził o ich kategoryzacji jako stosowanych i osadzonych w dyscyplinie nauk o bezpieczeństwie. Z celem procesu badawczego koresponduje pytanie badawcze – jakie rekomendacje i wnioski związane z miejscem ataku terrorystycznego mogą być kluczowe dla projektowania reakcji instytucjonalnej? Autor założył w hipotezie badawczej możliwość wyprowadzenia takich wniosków, które mogą przyczynić się do wzmocnienia jakościowej reakcji na współczesne ataki terrorystyczne. Opisane w tekście badania zostały oparte na metodach naukowych w postaci krytycznej analizy literatury, analizy dokumentów, analizy porównawczej, syntezy przekrojowej oraz wielokrotnych immersyjnych studiów przypadku. Uzyskane wyniki badań stały się podstawą do opracowania kluczowych wniosków, które powinny zostać uwzględnione w przygotowywaniu rozwiązań w zakresie instytucjonalnego reagowania na współczesne ataki terrorystyczne.
Współczesne zamachy terrorystyczne w aspekcie miejsca ich przeprowadzenia – wnioski do projektowania reagowania w wymiarze instytucjonalnym
Keywords: terrorism; responding to attacks; counter-terrorism; terrorist attack site; reagowanie na ataki; zwalczanie terroryzmu; terroryzm; miejsce ataku terrorystycznego